Menghadirkan Atribut Ketuhanan Sebagai Usaha Untuk Membangun Spiritualitas Umat Tuhan - Natalie, Natalie (Veritas : Jurnal Teologi dan Pelayanan, 2023)
Kevin Vanhoozer observes that the loss of imagination that is discipled and disciplined by the Bible leads many Christians to experience a disconnect between the world they live in and the world of the biblical texts they believe in. There is a gulf between known truth and lived practice. The daily lives of Christians do not bring out the resultant Christian character. This article attempts to explain the importance of meditating on the threefold lordship attributes proposed by John Frame—authority, control, and presence—in one’s daily meditation. It argues that one’s theological understanding is crucial in worldview formation and that, through intense meditation, those truths need to be internalized in the heart and mind so that they can be integrated into the practice of everyday life. This article also shows that the three inseparable lordship attributes need to be experienced in the relationship between spiritual leaders and the congregation, for true spirituality is formed not only in personal experience but also in the community. Such a pattern is then offered as a solution to answer challenges related to worship and fellowship during the pandemic and beyond. Through this article, it is hoped that the people of God can better understand the dynamics of their spiritual life, either through personal meditation or fellowship with other believers, either face-to-face or virtual meetings, including the role of a spiritual mentor whom first experiences and thus embodies God’s authority, control, and presence in their relationship with God’s congregation.